Implementation of an Evacuee Support System for Distributed Evacuation by Visualizing the Congestion Status of Evacuation Shelter - Tomoyuki Ishida; Ryosuke Nitama (Research Briefs on Information and Communication Technology Evolution, 2023)
We implemented an evacuee support system in this study. This system consists of evacuee’s safety information registration, evacuation shelter management, and evacuation shelter congestion status visualization systems. By implementing these three systems, a disaster response headquarters can manage the evacuees at each evacuation shelter accurately and quickly. Additionally, residents who are considering evacuating to evacuation shelters can browse the visualized congestion status of each evacuation shelter and move to vacant evacuation shelters. We evaluated the operability, readability, functionality, necessity, effectiveness, the applicability of the entire system, effectiveness and operability of the safety information registration system, readability and effectiveness of the evacuation shelter congestion status visualization system, and functionality and effectiveness of the evacuation shelter management system. We conducted evaluation experiments on 30 subjects and obtained a high evaluation in each evaluation item.